2017
DOI: 10.3168/jds.2016-11797
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of methicillin-resistant Staphylococcus aureus in dairy cattle herds, related swine farms, and humans in contact with herds

Abstract: In this study we investigated the circulation of methicillin-resistant Staphylococcus aureus (MRSA) in 2 dairy cattle farms (farm A and B), previously identified as MRSA-positive in bulk tank milk samples, and epidemiologically related to swine farms. Collected specimens included quarter milk samples and nasal swabs from dairy cows, pig nasal swabs collected at both the farm and slaughterhouse level, environmental dust samples, and human nasal swabs from the farms' owners and workers. The prevalence of MRSA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 39 publications
10
62
1
4
Order By: Relevance
“…The finding shows that overall prevalence of MRSA was 54% in the Pothohar region of Pakistan. Similar highlevel MRSA prevalence of 60%, was reported by Locatelli et al (2017). In contrast to our study lower MRSA prevalence (34%) in Pakistan (2017) was reported: while from other regions of the world a prevalence of 16.7%, and 9.2%, is reported from India (2011), Saudi Arabia (2018), respectively (Kumar et al, 2011;Aqib et al, 2017;El-Deeb et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…The finding shows that overall prevalence of MRSA was 54% in the Pothohar region of Pakistan. Similar highlevel MRSA prevalence of 60%, was reported by Locatelli et al (2017). In contrast to our study lower MRSA prevalence (34%) in Pakistan (2017) was reported: while from other regions of the world a prevalence of 16.7%, and 9.2%, is reported from India (2011), Saudi Arabia (2018), respectively (Kumar et al, 2011;Aqib et al, 2017;El-Deeb et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Apparent spread between species was observed using molecular and resistance typing of LA-MRSA, showing colonization of broilers, rats, dogs, cats, and farmers by strains highly similar to those in pigs on the same premises (Pletinckx et al, 2013). In a pattern already established for other contagious mastitis pathogens, poor hygiene at milking was observed to be associated with LA-MRSA spread between dairy cows (Locatelli et al, 2017).…”
Section: Drivers For Amrmentioning
confidence: 90%
“…Several studies examining the detection and/or subtyping of AMR bacteria have yielded evidence of the physical transfer of AMR between premises and between generations. This has been documented for LA-MRSA in pigs and cattle (Grøntvedt et al, 2016;Locatelli et al, 2017;Pletinckx et al, 2013), for cephalosporin-resistant E. coli in broilers (with hatcheries appearing to act as source and/or conduit in many cases) (Baron et al, 2018;Dierikx et al, 2013), and for FQ-resistant Campylobacter coli in broilers (Idris et al, 2006). An alternative (metagenomic) approach has yielded evidence of associations between the frequencies of certain AMR genes in feces, comparing breeding sows and their derived finishing herds on separate premises (Birkegård et al, 2018).…”
Section: Drivers For Amrmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, this is the first report of the detection of spa type t321 isolates in milk samples from cows with subclinical mastitis. Previously, it has only been isolated from humans, and swine [35][36][37], showing that the host specificity of the pathogen may be questioned.…”
Section: Discussionmentioning
confidence: 99%